The Remittance Engine: Decoding the Surge in Nepalese Labour-Driven Economy - Giri, Dan Bahadur (NPRC Journal of Multidisciplinary Research, 2026)
Background: Remittances refer to the payments sent by migrant workers to their home countries to help their families. They are commonly used to denote sums sent from both domestically and internationally, but the study focuses solely on external remittances. Likewise, the movement of Nepalese workers to various locations has become a widespread occurrence, and without readily exportable competitive products in global markets, remittances have emerged as a key source of foreign currency. Objective: This study aims to analyze the trend of labor migration from Nepal and the remittance-to-GDP ratio while investigating the relationship between remittance inflows and economic development, focusing on how increasing remittance inflows impact Nepal’s economic development. Methods: The research achieved its goal through the narrative review approach by exploring literature concerning remittance trends from publications in numerous journals, books, Ministry of Labour, Employment and Social Security series, Economic Survey, Ministry of Finance (MoF), foreign employment department, Government of Nepal, and releases from the World Bank, Nepal Rastra Bank, and more. Findings and Discussions: The average number of labour permits issued for the past ten years ranging from the fiscal years 2014/15 to 2023/2024 is 561,261. Similarly, the average Remittance to GDP Ratio for last ten years is 24.80 percent which supports the fact that remittance contributes one-fourth part of the national GDP. The financial, human, and social capital that migrant workers gather while abroad is connected; their amassed wealth has significant potential to greatly influence Nepal’s economic and social development. Conclusion and Recommendations: The financial, human, and social capital that migrant workers gather while abroad is connected; their amassed wealth has significant potential to greatly influence Nepal’s economic and social development. The Nepalese Government must prioritize optimizing remittances and effectively harnessing them for the holistic development of the nation, fostering a sustainable, joyful, and prosperous life for its citizens through enduring development initiatives. In addition to this, the government must create a strategy for a self-sustainable economy. Programs aimed at improving financial literacy for families receiving remittances can assist in directing funds towards savings, effective investments, and long-term asset development.